Urgensi Perjanjian Ekstradisi dalam Mengatasi Tindak Pidana Judi Online di Indonesia - I Kadek Agus Yudi Luliana (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the issue of online gambling in Indonesia and examine the urgency of extradition agreements as a legal instrument to prosecute online gambling operators who conduct their activities from abroad. Although gambling has been declared a criminal act under the Indonesian Criminal Code (KUHP) and the Electronic Information and Transactions Law (ITE Law), its enforcement has not been effective due to the transnational nature of this crime, in which gambling operators run their platforms from other countries, placing them beyond the direct reach of Indonesian jurisdiction. The research employs a normative legal methodology, examining statutory regulations, principles of criminal law, and relevant legal literature. The objects of study include the 1945 Constitution, the Criminal Code, and the ITE Law as the legal foundations for combating online gambling, as well as provisions concerning extradition within the framework of international cooperation. The findings indicate that although Indonesia normatively possesses legal grounds to prosecute perpetrators abroad through the principles of personality and protection, implementation remains hindered by state sovereignty and jurisdictional limits. Government efforts to block gambling websites have proven ineffective, as new sites continually emerge. Therefore, extradition agreements are essential and urgent as a solution to overcome jurisdictional barriers, enabling the transfer of offenders to Indonesia for prosecution and ensuring state protection for citizens from the harmful impacts of online gambling.